Effects of Blended Learning between Massive Open Online Course and Regular Conventional Course in Thailand’s University - Priyanut Wutti Chupradit, Nongluck Kienngam, Chanoknart Wongburanavart, Tharn Thongngok, Supat Chupradit (International Journal of Advanced Science and Technology, 2020)
This research aimed to study the effects of blended learning between massive open online course (Thai MOOC) and regular conventional course (with class attendance) by One Group Pretest - Posttest Design among 207 undergraduate students. The research instruments consisted of an online course on Thai MOOC: CMU017R the effective presentation technique. Data collection were pretest, posttest, students’ reflection evaluation, satisfaction evaluation form, and lesson plans. Mean and standard deviation of students’ achievement scores and Paired Samples t-test were analyzed. Moreover, student’s behaviors and satisfaction were analyzed and interpreted according to criteria from mean and standard deviation. The research findings were found as follows; posttest score after learning on Thai MOOC were significantly higher than before learning on Thai MOOC at 0.01 level. The most frequency of learning behaviors were 1) follow the learning activities according to course agreement; doing pretest, watching VDO, doing assignment respectively, 2) pay attention on learning both on Thai MOOC course and regular attendance and 3) emphasize both learning through MOOC course and regular attendance. In addition, the samples satisfied the learning activities that integrated with MOOC in class and they could learn anytime while the benefits of MOOC integration in classroom was being able to review the lessons at any time.